The reform of Brusells I bis Regulation. Possibilities and perspectives - Hess, Burkhard (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
According to Article 79 of Regulation (EU) 1215/2012, the EU Commission shall present a report on the application of the Brussels Ibis Regulation by 11 January 2022. This paper intends to open the discussion about the present state of affairs and the necessary adjustments of the Regulation. Although there is no need to change its basic structure, the relationship of the Brussels Ibis Regulation with other EU instruments (as the General Data Protection Regulation) should be reviewed. There is also a need to address third-State relationships and cross-border collective redress. In addition, the paper addresses several inconsistencies within the present Regulation evidenced by the case law of the CJEU: such as the concept of contract (Article 7.1), the place of damage (Article 7.2), the protection of privacy and the concept of consumers (Articles 17 - 19). Finally, some implementing procedural rules of the EU Member States should be harmonised, i.e. on the assessment of jurisdiction by national courts, on judicial communication and on procedural time limits. Overall, the upcoming review of the Brussels Ibis Regulation opens up an opportunity to improve further a central and widely accepted instrument of the European law of civil procedure.